KONSENTRASI AQUIFER DI ATAS TEROWONGAN KARETA API SASAKSAAT PADALARANG KABUPATEN BANDUNG DENGAN METODA GEOLISTRIK - Z, Fakhruddin (Jurnal Pilar Sains, 2007)
Expression process of under earth surface can be done variosly, one method used is resistivities methodwhich can be used in geothermal exploration, geotechnical application, ancient object seeking, seeking ofground water and others. Saturated water zone determination the above tunnel sasaksaat PadalarangBandung Regency very need, this matter done to know distribution aquifer and earth coat resistivitiesabove tunnel Sasaksaat. This research use Wenner-Schlumberger method with two trajectory direction,that is vertical trajectory of tunnel and unidirectional of tunnel. Obtained some saturated water zone, thisarea have very low resistivities. Generally each trajectory have saturation water point, among other thingsat straighten trajectory, trajectory 1 at 75 meters, trajectory 2 at 80 meters and trajectory 3 at 50 meterspoint. Each +- 10 meters depth from surface since near surface trajectory 3. Unidirectional trajectory mostsaturated water zone point 430 meter with deepness +-25 meters from surfaceKey word : Geoelektical Study, Wenner-Schlumberger method